Manifesto for Collections-Based Research and Teaching: Manifesto for Collections- Based Research and Teaching - Fleming, Martha (Periskop – Forum for kunsthistorisk debat, 2020)
Most of this manifesto refers to the PhD level, but elements of this training are applicable to BA and MA contexts as well. My point is that research activity is the most vital constituent of any successful university learning environment, and research environments are not unique to the university. It is a pedagogical position, not an institutional location, and since collecting institutions are crucial to the production of knowledge in many fields, we can find such learning spaces in most collecting institutions as well.